Oxidase-like nanozyme activity of ultrathin copper metal–organic framework nanosheets with high specificity for catechol oxidation - Singh, Ajit Kumar; Sharma, Deepika; Singh, Devesh Kumar; Sarraf, Sonu; Basu, Aviru Kumar; Ganesan, Vellaichamy; Saha, Avishek (ChemCatChem, 2025)
In nature, catechol oxidase catalyzes the oxidation of o-diphenol to o-quinone to produce a series of highly important polyphenolic natural products. Although mimicking the functionality of natural enzyme using a nanozyme was found to be beneficial, attaining a high specificity is challenging. Herein, we have explored the thickness-dependent oxidase activity and specificity of Cu-metal-organic framework (MOF) nanosheets. The unique synthetic method offers control over the thickness of the Cu-MOF nanosheets. The ultrathin (4 nm) Cu-MOF (Cu-UMOF) nanosheets as an oxidase nanozyme exhibit high specificity for catechol oxidation without having any peroxidase activity. Interestingly, the thicker (20–30 nm) Cu-MOF nanosheets showed poor catechol oxidase and peroxidase activity. The binuclear Cu-center, coordinative, and electronic unsaturation tuned electronic structure in Cu-UMOF, resulting in higher specificity for catechol oxidation than thicker Cu-MOF.